STUDY OF RAINFALL AND RIVER DEBIT INTERACTION USING RATIONAL METHOD TO DETERMINE INTRUSION OF SEA WATER IN THE JAKARTA BAY AREA - Lubis, Atika; Permadhi, Yan F; Haryanto, Eko (Jurnal Hidrosfir Indonesia, 2010)
The Ciliwung River that flow through Jakarta Province is one of important factor for the city. The deficiently water management in Jakarta caused water supply crisis within the area. The unsufficient water supply for Jakarta is causing groundwater pumping by the local people to comply their needs of water. Thus generated saline water intrusion from the Ciliwung’s downstream to the upstream through to the people’s settelement.The objective of this research is to find how far the sea water intrusion at Jakarta Bay by analyzing the interaction between rainfall with the Ciliwung River’s debit. Jakarta’s land cover is dominated by watertight materials such as concrete and asphalt induced runoff greater than infiltration. The current land cover caused the groundwater contaminated by sea water intrusion. The hypothesis is based on the groundwater calculation for Ciliwung’s River Basin. It showed the average ofbaseflow for the the Ciliwung’s River Basin range between 550 – 680 mm per year. The baseflow range shows that water absorbed by the ground is lesser than the rainfall at Ciliwung’s RiverBasin that ranged between 2000 – 2500 mm per year.Afterwards, using ten years of climate data and debit data from Katulampa Station (the Upstream of Sungai Ciliwung) and also using data from the Angke Estuary and the Ancol Estuary (Lower Ciliwung River) acquired the maximum sea water intrusion in Ciliwung River on May 6, 2005. The intrusion reaches is ranged between 14 – 20 kms measured from the downstream of Angke Estuary. While the intrusion at the Ancol Estuary ranged from 18 – 22 kms.